2020
DOI: 10.1017/s0007114520000124
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Dietary Approaches to Stop Hypertension (DASH) and hypertension risk: results of the Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: We investigated whether high adherence to the Dietary Approaches to Stop Hypertension (DASH) diet was independently associated with lower risk of incident hypertension. Participants included 5632 adults, without hypertension at the baseline (2008–2010) of the Longitudinal Study of Adult Health, who took part in the second follow-up visit (2012–2014). Adherence to the DASH diet was estimated at baseline using a score based on eight food items (final scores from 8 to 40 points) and was categorised as high adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 57 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…On the other hand, other studies found a negative association between a “Healthy” DP (such as the Prudent DP) and systolic BP, and lower occurrence of hypertension [ 32 ]. A recent longitudinal study in Brazil reported the protective effect of following a DP characterized by healthy food selection [ 58 ] in incident hypertension. Moreover, it found that body weight explained as much as 10% in the reduction risk of high BP.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other studies found a negative association between a “Healthy” DP (such as the Prudent DP) and systolic BP, and lower occurrence of hypertension [ 32 ]. A recent longitudinal study in Brazil reported the protective effect of following a DP characterized by healthy food selection [ 58 ] in incident hypertension. Moreover, it found that body weight explained as much as 10% in the reduction risk of high BP.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis on 30 randomized clinical trials observed that adherence to the DASH diet can significantly lower blood pressure in hypertensive and healthy adults [ 40 ]. Francisco et al, in their study, reported that adherence to the DASH diet was associated with a significant reduction in blood pressure, even with a short follow-up period [ 41 ]. Legumes, fruits and vegetables are enriched antioxidants and essential vitamins, including fibre, vitamin C, potassium, folic acid, magnesium, flavonoids, and carotenoids, and have synergistic effects on lowering blood pressure by improving endothelial function and their antioxidative properties causing vasodilation [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another RCT, Juraschek et al evaluated the effects of low versus high sodium, DASH versus control, and both (low sodium-DASH vs. high sodium-control diets) on SBP and found that the combination of reduced sodium intake and the DASH diet has lowered SBP throughout the range of pre-and stage 1 hypertension [42]. In two large cohort studies, adherence to the DASH dietary pattern was related to lower levels of DBP after 10 years of follow-up [43,44], while another recent longitudinal study associated adherence to the DASH diet with 26% lower risk of developing hypertension [45]. On the contrary to these findings, Divens et al [46] did not find any significant changes in SBP and DBP in African American women who followed the DASH dietary pattern for one year.…”
Section: Discussionmentioning
confidence: 99%